Peningkatan Kualitas Guru Bimbingan dan Konseling melalui Penguasaan Teori Realita - Cindy Asli Pravesti; Ayong Lianawati; Elia Firda Mufidah; Tamsil Muis; Sutijono Sutijono; Arifin Arifin; Pury Ayu Fitriya (Jurnal Pengabdian Pada Masyarakat, 2021)
IMPROVING THE QUALITY OF GUIDANCE AND COUNSELING TEACHERS THROUGH REALITY THEORY SKILLS. The importance of an effective quality counselor is the whole person of the counselor. This is indicated by the ability of the counselor’s performance through the approach or theory of guidance and counseling. It aims to improve the quality of the counselor’s performance through the reality therapy that can bring the full direction of the counselor's personality. Reality therapy directs the counselor’s personality to be responsibility, honest (reality), sincere (right) to facilitate counselors in conducting guidance and counseling services. The embodiment of this is carried out through community service activities. The method of activity used is an online workshop (webinar) with steps, the first is the initial step (observation), the planning stage, the socialization stage, and the ongoing evaluation stage of the program. The community service activities were attended by 255 participants. The results obtained in community service activities are that 55% have clear abilities, 43% have sufficient abilities, and 2% have less abilities. Thus, the form of contribution to the science of guidance and counseling and education is expected to be implemented (reality therapy) together with stakeholders in order to achieve optimal and comprehensive success.